Cortical Gyrification in Transgender Individuals. (13th March 2021) - Wang, Yanlu; Khorashad, Behzad S; Feusner, Jamie D; Savic, Ivanka
Abstract: Gender incongruence (GI) is characterized by a feeling of estrangement from the own body in the context of self. GI is often described in people who identify as transgender. The underlying mechanisms are unknown. Data from MRI measurements and tests of own body perception triggered us to pose a model that GI in transgender persons (TGI) could be associated with a disconnection within the brain circuits mediating the perception of own body as self. This is a departure from a previous model of sex atypical cerebral dimorphism, introducing a concept that better accords with a core feature of TGI. The present MRI study of 54 hormone naive transmen (TrM), 38 transwomen (TrW), 44 cismen and 41 ciswomen show that cortical gyrification, a metric that reflects early maturation of cerebral cortex, is significantly lower in transgender compared with cisgender participants. This reduction is limited to the occipito-parietal cortex and the sensory motor cortex, regions encoding own body image and body ownership. Moreover, the cortical gyrification correlated inversely with own body-self incongruence in these regions. These novel data suggest that GI in TGI may originate in the neurodevelopment of body image encoding regions. The results add potentially to understanding neurobiological contributors to gender identity.